Evaluation of selected parameters of rat liver injury following repeated administration of oseltamivir for different periods - Al-Rikabi, Falah Muosa Kadhim (The Iraqi Journal of Veterinary Medicine, 2012)
The effects of oseltamivir administration, an anti influenza viruses A and B, on somefunctional parameters of rat liver were investigated, to evaluate the possible hepatotoxiceffect. Eighteen (18) wister male albino rats with body weight ranged 150-190 gm weredivided into three groups, the first group(T1) was treated orally with 1mg/kg.BW astherapeutic dose of Oseltamivir for 7consuctive days. The second group (T2) wastreated with the same dose for six weeks, while the control group dosed distill water.The results revealed, there was a significant increase in the onset of barbiturate sleepingtime and a significant p ≤ 0.05 decrease of the duration of barbiturate sleeping time ofthe T2 rats . The liver enzymes activity revealed a significant decrease in ALT in T1rats and significant increased p<0.05 in the T2 rats, while the AST activity showed onlysignificant increased p<0.05 in the T2 treated rats. The activity of ALP was p<0.05significantly increased in the rats of treated groups. The blood sugar was significantlydecreased p<0.05 only in the T2rats. Cholesterol level was significantly p<0.05increased in T2 treated rats, while the serum of both treated groups showed asignificantly increase p<0.05 in the triacylglycerol concentration.The HDL level was significantly decreased p<0.05 only in theT1 rats. The treated T2rats showed a significant decrease p<0.05 in the LDL, while the VLDL level revealed asignificant increase p<0.05.The total serum protein level was significantly increasedp<0.05 in the rats of T2. Liver histopathological lesions of the T1rats revealed largeamount of suppurative exudates, severe dilation and congestion of central veins andsinusoids with activation of kupffer cells. The liver of T2 rat showed multiple areas offocal necrosis, fibrous thickening of Glisson capsule with vacuolar degeneration ofhepatic parenchyma. In:conclusion, Oseltamivir has hepatotoxic effect in rats treatedwith therapeutic dose 1mg/ kg.BW. orally in different periods.